1983
DOI: 10.1111/j.1365-2389.1983.tb00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation by white clover (Trifolium repens) in grasslands on soils contaminated with cadmium, lead and zinc

Abstract: The nitrogenase activity (potential nitrogen fixation) of a mixed white clover-grass sward growing on a range of soils containing up to 21 6 pg g-' Cd, 30 000 pg g-' Pb and 20 000 pg g-' Zn was determined using the acetylene-reduction assay. The plants were incubated in situ using an intact soil-core technique. Little change in the rate of CzH2 reduction was observed during the daylight hours although a marked seasonal fluctuation was found, the maximum activity during the spring and declining to 20% of this b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…Por outro lado, rizóbio eficiente foi isolado de nódulos de planta hospedeira nativa em solos contaminados, independentemente da concentração de metal (Martensson & Witter, 1990;Obbard et al, 1993), sugerindo que os bacteróides são protegidos dos efeitos tóxicos dos metais, no interior dos nódulos radiculares (Rother et al, 1983;McGrath et al, 1988;Giller et al, 1989;Smith & Giller, 1992).…”
Section: Introductionunclassified
“…Por outro lado, rizóbio eficiente foi isolado de nódulos de planta hospedeira nativa em solos contaminados, independentemente da concentração de metal (Martensson & Witter, 1990;Obbard et al, 1993), sugerindo que os bacteróides são protegidos dos efeitos tóxicos dos metais, no interior dos nódulos radiculares (Rother et al, 1983;McGrath et al, 1988;Giller et al, 1989;Smith & Giller, 1992).…”
Section: Introductionunclassified
“…Early studies showed symbiotic N 2 fixation to be unaffected by even very high soil concentrations of heavy metals (Rother et al, 1983). However, a number of 13 authors later reported it to be affected even at relatively low soil concentrations (Chaudri et al, 1993;Giller et al, 1998) 14 In addition to the compartmentalisation of Cd, plant organs possess other mechanisms of detoxifying Cd, e.g., phytochelatin synthesis (Sanitá di Toppi and Gabbrielli, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed symbiotic N 2 fixation to be unaffected by even very high soil concentrations of heavy metals (Rother et al, 1983). However, a number of authors later reported it to be affected even at relatively low soil concentrations (Chaudri et al, 1993;Giller et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The plant growth promoting rhizobacteria Kluyvera ascorbata sub165, which was isolated from heavy metal-contaminated soil in Canada, was found to protect canola (Brassica napus L.) against nickel (Ni), lead (Pb), zinc (Zn) and chromium (Cr) toxicity (Burd et al 1998). Jayakumar et al (2007) reported that increasing cobalt (Co) concentration from 50 to 250 mg kg -1 decreased the nitrogen content of Raphanus sativa L. Rother et al (1983) reported that excess cadmium and Pb reduced the nitrogen content of Trifolium repens L., while Gomes et al (1985) demonstrated that heavy metals reduced nitrate uptake by sorghum (Sorghum bicolor (L.) Moench.) roots.…”
Section: Discussionmentioning
confidence: 99%